2017
DOI: 10.1016/j.ica.2016.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate-templated synthesis of di-zinc macrocycles

Abstract: Herein we report that oxalate serves as a template in the formation of di-zinc macrocycles featuring bis(imino)pyridine chelating units linked by p-xylylene or m-xylylenes linkers. The resulting complexes were characterized by NMR spectroscopy, mass spectrometry, elemental analysis, and X-ray crystallography. NMR spectroscopy indicates highly symmetrical (C 2v or D 2h) structures of the macrocyclic complexes in solution. Solid-state structures, determined by X-ray crystallography (obtained only for the m-xylyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In the current study, we have investigated the ability of a dinucleating macrocyclic ligand framework to undergo dramatic geometric changes in response to the varying electronic requirements of the metal centers . This work makes use of 3 PDI 2 , a tert -butylated version of a macrocyclic, pyridyldiimine-based scaffold (Figure ) that we recently employed for mediating the putative formation of transient dicobalt bridging nitrides .…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we have investigated the ability of a dinucleating macrocyclic ligand framework to undergo dramatic geometric changes in response to the varying electronic requirements of the metal centers . This work makes use of 3 PDI 2 , a tert -butylated version of a macrocyclic, pyridyldiimine-based scaffold (Figure ) that we recently employed for mediating the putative formation of transient dicobalt bridging nitrides .…”
Section: Introductionmentioning
confidence: 99%
“…The metal–metal distances for ( 1 – 3 )­M 2 Br 4 are given in Table and range from 5.7600(8) to 6.232(1) Å. Similar distances were observed for macrocyclic bis-PDI complexes in which the PDI units are bridged by m -xylylene linkers, including ([ D ]­Cu 2 Im]­[CF 3 SO 3 ] 3 (Cu–Cu = 5.9181(9) Å), [ E ]­Zn 2 Ox]­[CF 3 SO 3 ] 2 (Zn–Zn = 5.3849(6) Å), ( F )­Zn 2 Cl 4 (Zn–Zn = 5.515(1) Å), and ( F )­Co 2 Cl 4 (Co–Co = 5.501(1) Å), which are shown in Chart . In contrast, the Co–Co distance in ( A )­Co 2 Cl 4 (R 1 = R 2 = H; 7.731(2) Å) is much longer. While the syn -double-decker complexes ( B )­Fe 2 Cl 4 have not been crystallographically characterized, Groysman has reported a similar [( B )­Co 2 (CH 3 CN) 4 ]­[Co­(CO) 4 ] 2 complex with a Co–Co distance of 4.628(1) Å .…”
Section: Resultsmentioning
confidence: 57%
“…Two early examples of bis-PDI complexes of this type, [( A )­M 2 Im]­[CF 3 SO 3 ] 3 (M = Cu or Ni), were prepared by Burrows as models for the Ni 2 active site in urease. These complexes were synthesized by reacting M­(OTf) 2 and imidazole (ImH) to form a putative [M–Im–M] 3+ complex, which was then added to a solution of 2,6-diacetylpyridine and m -xylylenediamine. More recently, Groysman showed that an analogous Zn complex, [( A )­Zn 2 Ox]­[CF 3 SO 3 ] 2 (Ox = oxalate), is formed using in situ -generated [Zn 2 Ox] 2+ as the binucleating template . The [Zn 2 Ox] 2+ template also directs the condensation of 2,6-formylpyridine and p -xylylenediamine to produce [( B )­Zn 2 Ox]­[CF 3 SO 3 ] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Groysman showed that an analogous Zn complex, [(A)Zn 2 Ox][CF 3 SO 3 ] 2 (Ox = oxalate), is formed using in situ-generated [Zn 2 Ox] 2+ as the binucleating template. 49 The [Zn 2 Ox] 2+ template also directs the condensation of 2,6-formylpyridine and p-xylylenediamine to produce [(B)Zn 2 Ox][CF 3 SO 3 ] 2 . It should be emphasized that the binucleating templates are critical for macrocyclization in the synthesis of [(A)M 2 Im][CF 3 SO 3 ] 3 and [(A)Zn 2 Ox]-[CF 3 SO 3 ] 2 .…”
Section: ■ Introductionmentioning
confidence: 99%